Robotic surgery for the upper gastrointestinal tract: Current status and future perspectives. Issue 4 (26th October 2017) - Nakauchi, Masaya; Uyama, Ichiro; Suda, Koichi; Mahran, Mohamed; Nakamura, Tetsuya; Shibasaki, Susumu; Kikuchi, Kenji; Kadoya, Shinichi; Inaba, Kazuki
Abstract: More than 4000 da Vinci Surgical Systems have been installed worldwide. Robotic surgery using the da Vinci Surgical System has been increasingly performed in the last decade, especially in urology and gynecology. The da Vinci Surgical System has not become standard in surgery of the upper gastrointestinal tract because of a lack of clear benefits in comparison with conventional minimally invasive surgery. We initiated robotic gastrectomy and esophagectomy for patients with upper gastrointestinal cancer in 2009, and we have demonstrated the potential advantages of the da Vinci Surgical System in reducing postoperative local complications after gastrectomy and recurrent laryngeal nerve palsy after esophagectomy. However, robotic surgery has the disadvantages of a longer operative time and higher costs than the conventional approach. In this review article, we present the current status of robotic surgery for gastric and esophageal cancer, as well as future perspectives on this approach, based on our experience and a review of the literature.